Granite and associated mafic phases, North River pluton, Cobequid Highlands, Nova Scotia - Pe-Piper, Georgia (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1991)
The North River pluton is one of a series of upper Devonian - lower Carboniferous granite and gabbro/diorite plutons in the Cobequid Highlands. It lies within a regional zone of east-west strike-slip faulting associated with the Cobequid Fault. The pluton consists of a single main granite unit that intruded small marginal bodies of gabbro. The southern part of the pluton is locally foliated and pervasively fractured. Diabase and microgranite sheets and dykes cut the pluton and adjacent country rock. A relative sequence of intrusion can be determined from cross-cutting relationships with foliated or fractured granite. Hybrid rocks demonstrate that some of the mafic magma was intruded synchronously with granitic magma. The pluton is geochemically similar to other Devono-Carboniferous plutons in the Cobequid Highlands, although it represents a deeper structural level than most of the other plutons. The granite is a subalkalic A-type granite. The mafic rocks show "within-plate" geochemical characteristics; early intrusions resemble olivine-normative continental tholeiites, but later dykes are highly fractionated and show strong enrichment in incompatible elements. Enrichment in Rb and K in the northeastern part of the pluton reflects a late metasomatic event associated with the growth of secondary biotite. The Devono-Carboniferous plutons of the Cobequid Highlands differ from other published examples of shear zone plutonism in that magma generation appears to have been related to either local or more probably regional extension rather than the shear zone having tapped a magma that originally resulted from either subduction or continental collision.